1998
DOI: 10.1128/mcb.18.12.7030
|View full text |Cite
|
Sign up to set email alerts
|

The T-Cell Oncogenic Protein HOX11 ActivatesAldh1Expression in NIH 3T3 Cells but Represses Its Expression in Mouse Spleen Development

Abstract: Hox11 is a homeobox gene essential for spleen formation in mice, since atrophy of the anlage of a developing spleen occurs in early embryonic development in Hox11 null mice. HOX11 is also expressed in a subset of T-cell acute leukemias after specific chromosomal translocations. Since the protein has a homeodomain and can activate transcription, it probably exerts at least some of its effects in vivo by regulation of target genes. Representational difference analysis has been used to isolate cDNA clones corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 44 publications
3
50
0
Order By: Relevance
“…1,[22][23][24]40,41 Our findings strongly suggested that TLX1 directly binds to noncoding satellite 2 DNA sequences in vitro as well as within leukemic T-cells (ALL-SIL) that harbour a chromosomal translocation involving the TLX1 locus at 10q24. Satellite 2 DNA is a poorly conserved, highly repetitive element found near the centromeres of chromosomes 1, 2, 7, 9, 10, 16, 22, Y and possibly 21, that altogether represents about 2% of the human genome.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…1,[22][23][24]40,41 Our findings strongly suggested that TLX1 directly binds to noncoding satellite 2 DNA sequences in vitro as well as within leukemic T-cells (ALL-SIL) that harbour a chromosomal translocation involving the TLX1 locus at 10q24. Satellite 2 DNA is a poorly conserved, highly repetitive element found near the centromeres of chromosomes 1, 2, 7, 9, 10, 16, 22, Y and possibly 21, that altogether represents about 2% of the human genome.…”
Section: Discussionmentioning
confidence: 95%
“…To date, several potential downstream targets of TLX1 have been identified by examining correlations in gene transcription following the enforced or blocked expression of this transcription factor in cells or transgenic mice. [22][23][24] This includes the genes encoding aldehyde dehydrogenase 1a1, Fhl1/Slim1, Wt1 and NR4A3. However, although the preferred in vitro binding sequence (CGGTAA T / G TGG) is known, 25,26 as yet no direct in vivo targets of TLX1 have been delineated.…”
Section: Introductionmentioning
confidence: 99%
“…The diminished expression of certain Wnt-induced and Wnt-related genes in HOX11 þ T-ALL and Jurkat/ MSCVhyg-HOX11 cells that was observed was in accordance with the documented ability of HOX11 to also act as a negative regulator of gene expression (Greene et al, 1998;Owens et al, 2003). To further investigate this observation, we next performed luciferase reporter assays in 293 T cells using the TOPflash luciferase reporter plasmid.…”
Section: Validation Of Microarray Data and Hox11 Transcriptional Mechmentioning
confidence: 93%
“…The above results notwithstanding, it is necessary to underscore the fact that HOX11 regulation of ISREcontrolled transcription was dependent on an intact homeodomain as is the expression of the HOX11 target gene Aldh1 (Greene et al, 1998;Owens et al, 2003). Using hematopoietic precursor cell immortalization as a surrogate transformation assay (Hawley et al, 1994a(Hawley et al, , 1997, our laboratory previously reported that deletion of the third helix of the homeodomain (HOX11 H3d mutant) or the introduction of point mutations within helix 3 (e.g., HOX11Asn51Ala mutant) abrogated HOX11 immortalizing function .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation